2022
DOI: 10.1029/2021jd035473
|View full text |Cite
|
Sign up to set email alerts
|

Review of Brown Carbon Aerosols in China: Pollution Level, Optical Properties, and Emissions

Abstract: Brown carbon (BrC) is conventionally defined as a collection of substantially light-absorbing organic aerosols (OAs; Andreae & Gelencsér, 2006). In contrast to black carbon (BC), the absorption of BrC has a strong wavelength dependence, which peaks in the ultraviolet (UV) spectral region and declines through the visible spectral region (Andreae & Gelencsér, 2006). Atmospheric BrC plays a substantial role in the earth-atmosphere energy balance. It can scatter and absorb solar radiation (direct effect), modify c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 162 publications
0
11
0
Order By: Relevance
“…While this study reports the first measurements of the quantum yields and steady-state concentrations of values reported in our study serve as lower limits since they were measured using extracts comprised of only the water-soluble fraction of PM 2.5 . Water-insoluble BrC, which reportedly dominates the total BrC absorption in some parts of China (Bai et al, 2020;Huang et al, 2020;Wang et al, 2022), will likely produce 1 O 2 and 3 C * as well. Second, due to limited extract volumes for photochemical experiments and chemical analysis, only one 3 C * chemical probe was used in our study to quantify 3 C * quantum yields, formation rates, and steady-state concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…While this study reports the first measurements of the quantum yields and steady-state concentrations of values reported in our study serve as lower limits since they were measured using extracts comprised of only the water-soluble fraction of PM 2.5 . Water-insoluble BrC, which reportedly dominates the total BrC absorption in some parts of China (Bai et al, 2020;Huang et al, 2020;Wang et al, 2022), will likely produce 1 O 2 and 3 C * as well. Second, due to limited extract volumes for photochemical experiments and chemical analysis, only one 3 C * chemical probe was used in our study to quantify 3 C * quantum yields, formation rates, and steady-state concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the molecular diversity of BrC compounds and the complexity of atmospheric conditions, BrC undergoes dynamic changes in the atmosphere, leading to regional variations in its impact on climate. , Given the potentially higher BrC emission in China (BrC columnar mass concentration: 4.4–92 mg m –2 ) than in Europe and North America (BrC columnar content: around 5 mg m –2 ), more comprehensive studies are required to fully elucidate the chemical composition and light absorption properties of BrC in different Chinese cities. , Moreover, research on the seasonal variation of BrC remains limited. In this study, aerosol samples were collected in six Chinese megacities, including Beijing, Harbin, Xi’an, Chengdu, Guangzhou, and Wuhan, in winter and summer, to investigate the light absorption properties, chemical species, and molecular composition of BrC.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate the formation mechanism of BrC in the troposphere, synchronous observations on atmospheric BrC were conducted on the mountainside and the mountain foot of Mt. Hua, which is located closely to Guanzhong Basin, one of the areas with heaviest PM2.5 pollution in China owing to intensive activities of fossil fuel combustion and the unfavorable topography (Wang et al, 2022b;Wu et al, 2020;Wang et al, 2011;Wang et al, 2016). Our previous study has shown that inorganic aerosol chemistry in the atmosphere over Mt.…”
Section: Introductionmentioning
confidence: 99%